2014
DOI: 10.1128/cvi.00263-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Antibody Levels 7 to 9 Years after Booster Vaccination in Alaska Native Persons

Abstract: Hepatitis B antibody persistence was assessed in individuals who had previously received a vaccine booster. We measured hepatitis B surface antigen antibody (anti-HBs) levels 7 to 9 years post-hepatitis B booster in individuals with primary vaccination at birth. While 95 (91.3%) of 104 participants had detectable anti-HBs (minimum, 0.1 mIU/ml; maximum, 1,029 mIU/ml), only 43 (41%) had protective levels of >10 mIU/ml. Pre-and week 4 postbooster anti-HBs levels were significant predictors of hepatitis B immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
2
12
1
Order By: Relevance
“…Some studies have suggested that the levels of anti-HBs decrease after a full HB vaccination schedule [34]. Further studies are needed to evaluate the persistence of immune responses generated by 10 and 5 g HB vaccines.…”
Section: Tablementioning
confidence: 99%
“…Some studies have suggested that the levels of anti-HBs decrease after a full HB vaccination schedule [34]. Further studies are needed to evaluate the persistence of immune responses generated by 10 and 5 g HB vaccines.…”
Section: Tablementioning
confidence: 99%
“…[ 3 4 ] In the Middle East and North Africa, the prevalence of HBV infection is different such as 7.4% in Iran, 9.8% in Egypt, 6.9% in Libya, 2.4% in Lebanon, 2.6% in Palestine, 8.6% in Israel, and 6.1% in Saudi Arabia. [ 5 ] In North America, 41% had anti-hepatitis B surface (HBs) levels of >10 mIU/ml 7–9 years after booster vaccination at birth,[ 6 ] even 51% had these protective levels 30 years after receiving the primary series without subsequent doses. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In studies in which immune memory was shown by means of the increase in anti-HBs after booster vaccination, anti-HBs titres were mostly measured only once and at rather different time points, ranging from 10 days to 2 months post-booster [7,[18][19][20][21]. In addition, in some studies anamnestic response was defined as an increase in anti-HBs to ≥10 IU/l [21][22][23][24][25], in other studies as 4-fold increase in anti-HBs [5], and sometimes both criteria were applied [13,15,20,26]. Because of the differing definitions, it seems to be impossible to differentiate in all cases between anamnestic responses due to the presence of immune memory and primary responses after loss of immune memory.…”
Section: Introductionmentioning
confidence: 99%